Thermal stability of AlCoFeMnNi high-entropy alloy. (15th March 2019) - Karati, Anirudha; Guruvidyathri, K.; Hariharan, V.S.; Murty, B.S.
Abstract: The present study reports a modification in the composition of the well-studied AlCoCrFeNi high-entropy alloy (HEA), by replacing Cr with Mn. AlCoFeMnNi alloy was made by vacuum arc melting and its thermal stability behaviour was studied. The as-cast structure exhibited B2 phase. Upon heat treatment at 1050 °C for 50 h, it gave rise to a disordered B2 and FCC phases. Calphad (CALculation of PHAse Diagrams) studies using TCHEA (v2.1) database predicted formation of B2 and FCC phases. Due to absence of embrittling σ-phase, wider applicability of the alloy is possible. Graphical abstract: Unlabelled Image